Pengaruh Language Experience Approach (LEA) Berbantuan Media Gambar Berseri Terhadap Kemampuan Menulis Karangan Narasi Siswa Kelas IV - Anti Damayanti Kosasih; Indah Nurmahanani; Sofyan Iskandar (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research is based on students who have difficulty writing narratives. The purpose of this study is to determine students' ability to write narratives before using the language experience approach assisted by serial image media; students' ability to write narratives after using the language experience approach assisted by serial image media; and the effect of the language experience approach assisted by serial image media on students' ability to write narratives. The research sample was 4th grade elementary school students in Karawang, and the type of research used was a quasi experiment that was not comparable to the control group. The type of research used in this study is a quasi-experimental non-equivalent control group design, with the sample of this study being 4th grade elementary school students in Karawang. Based on the results of the study, it can be concluded: 1) the average score on the pretest of the experimental class and the control class is low, and there is no difference in the average score; 2) after applying the language experience approach assisted by serialized picture media, there is a difference in the posttest results of the experimental class and the control class. Then there was an increase in posttest scores in the experimental class. This can be seen from the results of descriptive analysis and inferential analysis, but the average value is still categorized as low; 3) There is a significant effect on students' narrative essay writing ability after applying the language experience approach assisted by serialized picture media. Keywords : Writing skill; Language Experience Approach; Series Pictue; Narrative.